2008
DOI: 10.1186/1755-8794-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker expression patterns that correlate with high grade features in treatment naive, organ-confined prostate cancer

Abstract: Background: The early detection of prostate cancer has resulted in an increase in the number of patients with localized prostate cancer and has paralleled the reported reduction in prostate cancer mortality. The increased rate of detection of patients with localized prostate cancer may also increase the risk of potentially morbid therapy in a patient with indolent cancer. Defining the biomarker correlates of prostate cancer virulence will facilitate the appropriate application and development of therapy for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…25 Subsequent loss of p53 leads to hyperproliferative phenotypes in several cancer cell lines. 2628 Collectively these studies point toward an important influence of Pim-1 expression to increase cell cycling, but the role of Pim-1 on CPC proliferation has yet to be elucidated. To determine whether Pim-1 enhances CPC cycling, control nontransgenic mice (NTG) were compared to 3 genetically engineered mouse lines with altered Pim-1 activity: cardiac-specific overexpression of Pim-1 (Pim-wt), a kinase dead form of Pim-1 (Pim-DN), 9 and Pim-1–null mice (Pim-KO).…”
mentioning
confidence: 99%
“…25 Subsequent loss of p53 leads to hyperproliferative phenotypes in several cancer cell lines. 2628 Collectively these studies point toward an important influence of Pim-1 expression to increase cell cycling, but the role of Pim-1 on CPC proliferation has yet to be elucidated. To determine whether Pim-1 enhances CPC cycling, control nontransgenic mice (NTG) were compared to 3 genetically engineered mouse lines with altered Pim-1 activity: cardiac-specific overexpression of Pim-1 (Pim-wt), a kinase dead form of Pim-1 (Pim-DN), 9 and Pim-1–null mice (Pim-KO).…”
mentioning
confidence: 99%
“…Inguinal adipose tissue of mice fed high fat diet (HFD) was analyzed and Pcyt2 was found to be up-regulated in high fat gainers on HFD in comparison to low fat gainers on the same diet. Pcyt2 expression was also up-regulated in proximal and middle part of small intestine in mice fed high fat diet (HFD) for 2–8 weeks in comparison to the control animals fed low-fat diet [54]. Immunochemical analysis revealed that villi in the small intestine were enlarged in mice fed HFD.…”
Section: Pcyt2 Expression In the Metabolic Syndrome And Related DImentioning
confidence: 99%
“…Immunochemical analysis revealed that villi in the small intestine were enlarged in mice fed HFD. In these mice, the number of cells per villus and body length was higher, a characteristics that may function to extend the capacity of lipid absorption [54]. Increased cell proliferation requires increased phospholipid synthesis which could explain up-regulation of Pcyt2 expression.…”
Section: Pcyt2 Expression In the Metabolic Syndrome And Related DImentioning
confidence: 99%
“…Although the causal relationship between inflammation, innate immunity and cancer is more widely accepted, many of the molecular and cellular mechanisms mediating this relationship remain unresolved (Coussens and Werb, 2002). Many studies have implicated Nrf2 (Nfe2l2) in cancer (Ramos-Gomez et al, 2001;Katsuoka et al, 2005;Sporn and Liby, 2005;Nair et al, 2007a;Pearson et al, 2008) or inflammation-associated diseases such as colitis (Khor et al, 2006;Osburn et al, 2007), and Parkinson's disease (Clements et al, 2006), and NF-kB in inflammation (Muller-Ladner et al, 2002;Profita et al, 2008;Puthia et al, 2008) and cancer Cilloni et al, 2006;Sun and Zhang, 2007;McDonnell et al, 2008). Indeed, the identification of combinatorial, or synergistic, transcription factors and the elucidation of relationships among them are of great importance for understanding transcriptional regulation as well as transcription factor networks (Hu et al, 2007).…”
Section: A Putative Model For Nrf2 -Nfkb1 Interactions In Inflammatiomentioning
confidence: 99%